2000
DOI: 10.1016/s0377-2217(99)00245-3
|View full text |Cite
|
Sign up to set email alerts
|

A simplified ozone model based on fuzzy rules generation

Abstract: In this paper, simplified ozone models for potential use in integrated assessment are developed from the EMEP ozone model. which is a single-layer Lagrangian trajectory model. The simplification method uses fuzzy rule generation methodology to represent numerous results of the EMEP model as a response surface describing the source-receptor relationships between ozone precursor emissions and daily tropospheric ozone concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In the first step, since multiphase deterministic 3D modelling systems ( [29,30]) cannot be used to compute pollutant concentrations and air quality indexes, due to the required computational cost and the number of simulations needed to solve a multi-objective problem, they have been substituted by statistical surrogate models, identified processing the results of a set of Chemical Transport Models simulations ( [31][32][33]). In particular, following the methodologies presented in [34][35][36], models based on Artificial Neural Networks (ANNs), have been applied, mainly due to their features of low computational requirements, good performances and ability to reproduce non-linear functions.…”
Section: Multi-objective Model Setupmentioning
confidence: 99%
“…In the first step, since multiphase deterministic 3D modelling systems ( [29,30]) cannot be used to compute pollutant concentrations and air quality indexes, due to the required computational cost and the number of simulations needed to solve a multi-objective problem, they have been substituted by statistical surrogate models, identified processing the results of a set of Chemical Transport Models simulations ( [31][32][33]). In particular, following the methodologies presented in [34][35][36], models based on Artificial Neural Networks (ANNs), have been applied, mainly due to their features of low computational requirements, good performances and ability to reproduce non-linear functions.…”
Section: Multi-objective Model Setupmentioning
confidence: 99%
“…So, it is required to identify simplified models synthesizing the relationship between the precursor emissions and ozone concentrations. In literature source-receptor relationships have been described using ozone isopleths (Shih et al, 1998), or with reduced form models such as (a) simplified photochemical models, adopting semi-empirical relations calibrated with experimental data (Venkatram et al, 1994), and (b) statistical models, identified on the results of complex 3D Chemical Transport Models (Friedrich and Reis (2000), Ryoke et al (2000), Guariso et al (2004)). Therefore, all of these approaches do not consider the strategic issue due to the fact that different decisions can be taken in different times, making the optimization, essentially static.…”
Section: Introductionmentioning
confidence: 99%
“…Another way of optimal granulation are fuzzy functions and similar notions. Examples are the papers by Foody (1992) and Ryoke et al (2000).…”
mentioning
confidence: 99%